Total hip arthroplasty performed in summer is not associated with increased risk of revision due to prosthetic joint infection: a cohort study on 58 449 patients with osteoarthritis from the Danish Hip Arthroplasty Register - R. Joanroy; R. Joanroy; J. K. Møller; J. K. Møller; S. Gubbels; S. Overgaard; S. Overgaard; C. Varnum; C. Varnum (Journal of Bone and Joint Infection, 2024)
Aims: Danish surveillance data indicated a higher risk of revision due to prosthetic joint infection (PJI) following total hip arthroplasty (THA) performed during the summer season. We investigated the association between summer and revision risk following primary THA. Methods: This study identified 58 449 patients from the Danish Hip Arthroplasty Register (DHR) with unilateral primary THA due to osteoarthritis from 2010–2018. From Danish Health Registries, we retrieved information on Charlson Comorbidity Index (CCI), immigration, and death and microbiological data on intraoperative biopsies and cohabitation status. Meteorological data were received from the Danish Meteorological Institute. Summer was defined as June–September, and THAs performed during October–May were used as controls. The primary outcome was revision due to PJI: the composite of revision with ≥2 culture-positive biopsies or reported PJI to the DHR. The secondary outcome was any revision. The cumulative incidences of revision and the corresponding adjusted relative risk (RR) with 95 % confidence intervals (CI) were calculated by season of the primary THA. Results: A total of 1507 patients were revised, and 536 were due to PJI. The cumulative incidence for THAs performed during summer and the rest of the year was 1.1 % (CI 1.0–1.3) and 1.1 % (CI 1.0–1.2) for PJI revision and 2.7 % (CI 2.5–3.0) and 2.5 % (CI 2.4–2.7) for any revision, respectively. The adjusted RR for THAs performed during summer vs. the rest of the year for PJI revision and any revision was 1.1 (CI 0.9–1.3) and 1.1 (CI 1.0–1.2), respectively. Conclusion: We found no association between summer and the risk of PJI revision or any revision in a northern European climate.